(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article is called "Using modular technologies in the educational process in professional educational institutions", and the procedure for using modular technologies in professional educational institutions is mentioned in the article. The conclusion of the article summarizes the role of the professional educational institution in society, the advantages of using modular technologies in the educational process, and the procedure for using modular technologies.